Use of Artificial Intelligence Platforms in Middle School Level Arabic Language Learning - Zakiyah (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
The research investigates the integration of AI platforms in teaching Arabic at the middle school level, examining both its benefits and challenges. Employing a mixed-methods approach, combining qualitative and quantitative techniques such as observation, interviews, and documentation, the study gathers insights from various stakeholders including the principal, Arabic teacher, and ten students. Results indicate the effectiveness and user-friendliness of AI platforms in Arabic learning, identifying key factors influencing their utilization. Educators benefit from factors like network accessibility, device availability, training opportunities, and AI applications, while students' support factors include educators, parental involvement, device access, internet availability, and AI tools. Challenges faced by educators encompass limited internet access, infrastructure issues, and student awareness gaps. However, the advantages for educators are significant, including enhanced content delivery, innovative teaching methods, and time efficiency. The study underscores the importance of educators embracing technological advancements to enrich learning experiences. Recommendations emphasize the necessity for educational institutions to furnish adequate resources, offer training programs, and promote awareness among both educators and students to fully harness the potential of AI platforms like Google, thereby optimizing educational outcomes.